Historical disaster experiences: towards a comparative and transcultural history of disasters across Asia and Europe - Schenk, Gerrit Jasper (Transcultural research - Heidelberg studies on Asia and Europe in a global context, 2017)
Historical disaster research is still a young field. This book discusses the experiences different cultures, from Europe across the Near East to Asia, have of natural disasters. It focuses on the pre-industrial era and on the question of similarities, differences and transcultural dynamics in the cultural handling of natural disasters. Which long-lasting cultural patterns of perception, interpretation and handling of disasters can be determined? Have specific types of disasters changed the affected societies? What have people learned from disasters and what not? What adaptation and coping strategies existed? Which natural, societal and economic parameters play a part? The book not only reveals the historical depth of present practices, but also reveals possible comparisons that show globalization processes, entanglements and exchanges of ideas and practices in preMit bestem Dank im voraus-modern times